2015
DOI: 10.1111/odi.12376
|View full text |Cite
|
Sign up to set email alerts
|

Novel EDA mutation in X‐linked hypohidrotic ectodermal dysplasia and genotype–phenotype correlation

Abstract: This study extended the mutation spectrum of XLHED and revealed the relationship between genotype and the number of missing permanent teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…Although patients with HED always have similar clinical features, deviations in the degree of severity are observed (Schneider et al, 2011;Zhang et al, 2011;Burger et al, 2014;Wohlfart et al, 2016a). Zeng et al (2015) and Gaczkowska et al (2016) found that HED patients with truncating EDA mutations tend to lose more permanent teeth than patients with nontruncating mutations, while missense mutation patients likely lose fewer permanent teeth than patients with other types of mutations. Our study revealed that patients with EDA missense mutations had a higher frequency of hypohidrosis (P = 0.021).…”
Section: Discussionmentioning
confidence: 99%
“…Although patients with HED always have similar clinical features, deviations in the degree of severity are observed (Schneider et al, 2011;Zhang et al, 2011;Burger et al, 2014;Wohlfart et al, 2016a). Zeng et al (2015) and Gaczkowska et al (2016) found that HED patients with truncating EDA mutations tend to lose more permanent teeth than patients with nontruncating mutations, while missense mutation patients likely lose fewer permanent teeth than patients with other types of mutations. Our study revealed that patients with EDA missense mutations had a higher frequency of hypohidrosis (P = 0.021).…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, however, all four females with XLHED were recognized prenatally, there was no false negative result. This may, in part, be attributed to the small sample size and the genotype of affected female fetuses: three of them carry an EDA variant known to be associated with severe oligodontia (two large deletions and a mutation destroying the furin cleavage site of EDA1, respectively) . The sensitivity of tooth germ sonography is probably lower in affected female subjects who do not lack many teeth, and this may represent a potential limitation of the method.…”
Section: Discussionmentioning
confidence: 99%
“…Genotype‐phenotype correlation may also help to explain why one male fetus with XLHED was missed in the prenatal assessments. This subject carries an EDA variant, which results in the replacement of a potentially less critical amino acid in the tumor necrosis factor (TNF) homology domain of EDA1, and seems to be associated with less severe oligodontia; his 5‐year‐old brother with the same mutation (subject M26) has 11 teeth. Thus, in case of missense mutations known to lead to milder symptoms, tooth germ sonography must be performed with particular attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA was extracted and then subjected to polymerase chain reaction (PCR) and Sanger sequencing. The methods used for DNA extraction, PCR, and Sanger sequencing have been described in our previous studies . The primer sequences that were used are shown in Supporting Information Table S1.…”
Section: Methodsmentioning
confidence: 99%